The effect of network-based education on critical thinking skills of nursing students (Journal of Pharmaceutical Negative Results, 2023)
Introduction and aim: Critical thinking is a style of thinking that requires new and student-oriented education. Nursing mentors should try to train students interested in continuous learning according to the current conditions of clinical settings. This study was conducted with the aim of determining the effect of network-based learning on the critical thinking skills of nursing students studying at the Islamic Azad University of Golestan province in 2022.Method: This is an experimental pre/post-test study with two intervention and control groups, which was conducted on undergraduate nursing students studying at Islamic Azad University of Golestan in 2022. Convenience sampling method was used in this study to collect the sample. A total of 50 students participated in this study, who were divided into two intervention and control groups by simple random allocation method found on the website. Data collection tools in this study included the demographic information form and the critical thinking disposition inventory (CTDI).Findings: Before the intervention, the mean score of critical thinking was 343.76 ± 12.73 in the intervention group and 343.76 ± 12.73 in the control group, which showed no statistically significant difference (P=0.2). After the intervention, the mean score of critical thinking was 373.28 ± 18.55 in the intervention group and 340.2 ± 10.38 in the control group, which showed no statistically significant difference between the two groups (P<0.001).Conclusion: The findings of this study showed that problem solving training through virtual means can be effective in improving the critical thinking of nursing students. Perhaps the use of this method can have a significant effect on education of students and consequently, improve the quality of nursing care.